2022
DOI: 10.1029/2022je007228
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Venusian Mesoscale Cloud Morphology Between Images Acquired at Various Wavelengths

Abstract: The differences and similarities in morphologies acquired across various wavelengths in simultaneously obtained Venus' dayside images may provide clues on cloud/atmospheric physics and chemistry. Here, we focus on spatial scales smaller than ∼600 km, where cell‐like or streaky features seem to dominate in ultraviolet images. Using images acquired at ultraviolet wavelengths of 283 nm, 365 nm, and infrared wavelengths of 0.90, 2.02, and 10 μm by the Venus orbiter Akatsuki, correlation coefficient maps between pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The 2.02-μm morphology might reflect atmospheric vertical motions and is thus suitable for the present assessment. Narita et al (2022) showed that the UV morphology and the 2.02-μm morphology are highly anti-correlated; dark regions in UV images correspond to bright (high-cloud) regions in 2.02-μm images.…”
Section: Spatial Structure Of Mesoscale Morphologymentioning
confidence: 98%
See 2 more Smart Citations
“…The 2.02-μm morphology might reflect atmospheric vertical motions and is thus suitable for the present assessment. Narita et al (2022) showed that the UV morphology and the 2.02-μm morphology are highly anti-correlated; dark regions in UV images correspond to bright (high-cloud) regions in 2.02-μm images.…”
Section: Spatial Structure Of Mesoscale Morphologymentioning
confidence: 98%
“…Narita et al. (2022) showed that the UV morphology and the 2.02‐μm morphology are highly anti‐correlated; dark regions in UV images correspond to bright (high‐cloud) regions in 2.02‐μm images.…”
Section: Spatial Structure Of Mesoscale Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the cloud top decreases from low and middle latitudes to high latitudes (Haus et al., 2014). In the equatorial region, clouds are more patchy and spatially variable, possibly related to convective activities and waves (Narita et al., 2022; Titov et al., 2008). At middle and high latitudes, cloud spatial patterns are smoother and characterized by streaks and bands, suggesting convectively stable layers there (Titov et al., 2008).…”
Section: Motivationmentioning
confidence: 99%
“…The absorption at 283 nm is due not only to the unknown absorber but also to SO 2 . Thus, the small‐scale features at both wavelengths are positively correlated (Narita et al., 2022), but the correspondence of small‐scale features is not perfect. The winds obtained at the two wavelengths agreed well when the cloud features captured were nearly identical, but when they differed, the zonal winds obtained at 283 nm were almost always faster than those obtained at 365 nm.…”
Section: Introductionmentioning
confidence: 99%